2022
DOI: 10.1111/lapo.12194
|View full text |Cite
|
Sign up to set email alerts
|

The illusion of choice: Organizational dependency and the neutralization of university sexual assault complaints

Abstract: In response to new regulations, universities have created multiple options for managing sexual misconduct complaints. These options are described as maximizing survivors' autonomy through feminist paradigms of choice. This study uses data from ethnographic observation and 76 interviews with survivors, perpetrators, and administrators to examine whether providing options gave survivors control over their complaints. The findings indicate that survivors found the complicated and vague sexual misconduct policies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Study participants reported that the new regulations narrowed their response field under Title IX, and they anticipated resorting to other employee policies (e.g., Title V) to address the shortfalls in protection. Other researchers have found that the use of multiple options for managing sexual misconduct complaints can confuse and overwhelm survivors, increase their dependency on Title IX personnel, and undermine their autonomy and agency (Bedera, 2022). A number of Title IX coordinators in this study similarly thought the changes brought on by the new regulations would further undermine their credibility as a reliable and supportive force for survivors and the broader campus community.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants reported that the new regulations narrowed their response field under Title IX, and they anticipated resorting to other employee policies (e.g., Title V) to address the shortfalls in protection. Other researchers have found that the use of multiple options for managing sexual misconduct complaints can confuse and overwhelm survivors, increase their dependency on Title IX personnel, and undermine their autonomy and agency (Bedera, 2022). A number of Title IX coordinators in this study similarly thought the changes brought on by the new regulations would further undermine their credibility as a reliable and supportive force for survivors and the broader campus community.…”
Section: Discussionmentioning
confidence: 99%
“…Symbolic compliance has been a starting point to examine institutional commitments to meeting Title IX obligations in colleges and universities (Bedera, 2022). Gualtieri (2020) examined symbolic compliance of Title IX interpretations based on the 2011 Dear Colleague Letter about sexual harassment and sexual violence at 250 colleges and universities.…”
Section: Symbolic and Substantive Compliancementioning
confidence: 99%
“…She found that institutions used symbolic compliance in ways that differed based on institutional factors. Bedera (2022), looking further into Title IX and sexual This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Symbolic and Substantive Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…However, many implemented strategies have had limited or short-term effects (DeGue et al 2014; Jouriles et al 2018), and most college campuses’ social and built environments still provide opportunities for sexual violence (Armstrong, Hamilton, and Sweeney 2006; Boswell and Spade 1996; Hirsch and Khan 2020; Martin and Hummer 1989). In addition, university processes for handlingcomplaints of sexual assault and helping survivors are often inadequate and even counterproductive (Bedera 2022; Cruz 2020; Khan et al 2021; Nesbitt and Carson 2021).…”
mentioning
confidence: 99%